Factors Associated with Catch-up Growth in Term, Asymmetrical Small-for-Gestational Age Infants in the First Year of Life - Sundar Sivakumar; Thasma Santhanakrishnan Arunprasath; Padmasani Venkat Ramanan (Rambam Maimonides Medical Journal, 2021)
Introduction: Catch-up growth (CUG) in small-for-gestational age (SGA) infants is essential for their overall development. Knowledge about the factors influencing CUG might be critical in their effective management. Hence this study was performed with the aim of identifying factors that may influence CUG in SGA infants. Methods: Asymmetrical SGA infants born at term were included in the study as per defined criteria, and their demographic details were recorded. Anthropometric data, feeding practice details, and intercurrent illnesses data were collected on follow-up at 6 weeks, 6 months, and 12–15 months of age. Catch-up growth weight was defined as improvement of weight to the normal range of −2 to +2 weight-for-age Z score (WAZ). Analysis was carried out using SPSS Expand 17 software. Chi-square test was used to find association between variables. Logistic regression analysis was used to measure effect. A P value of less than 0.05 was taken as significant. Results: Out of 324 SGA infants born at term, 119 completed 12–15-month follow-up, of which 69.7% had achieved CUG weight. Exclusive breastfeeding >4 months, continued breastfeeding until 12–15 months, and absence of diarrheal episodes were positively associated with CUG. Pregnancy-induced hypertension, gestational diabetes, and maternal overweight/obesity were negatively associated with CUG. Maternal education status, conception age, gravida status, mode of delivery, vitamin D and iron supplementation, and intercurrent respiratory infections were not associated with CUG. On multivariate analysis, continued breastfeeding and absence of diarrheal episodes were independent factors associated with CUG. Conclusion: Breastfeeding practice, especially continued breastfeeding, and the absence of diarrheal illness are the key determinants for achieving CUG weight in term SGA infants, particularly in settings where resources are limited.